Analisis Nilai Tambah Produk Tahu di UD Sri Rahayu, Kabupaten Bulungan - Moh. Wahyu Agang; Muh. Adiwena (Universitas Wahid Hasyim, 2025)
The agroindustry is a key driver of Indonesia's economy, especially in small and medium enterprises. One of the most widely consumed agroindustrial products is tofu, which has a high consumption rate among the population. This study want to measure the value creation by the tofu industry at UD Sri Rahayu, Bunyu Island, North Kalimantan, and its impact on neighborhood economy. This study utilizes qualitative analysis and value-added assessment. The findings reveal that each kilogram of processed soybeans yields 1.5 kg of tofu, with an added value of IDR 8,495 per kg. About 25.25% of the added value is allocated to labor, while 74.75% contributes to the business owner's profit. Given the high profit margin, this industry has the potential for further growth through improved production efficiency and product diversification. This research aims to offer valuable perspectives for tofu entrepreneurs and policymakers to enhance the competitiveness and sustainability of Indonesia’s tofu industry.